Country ownership of reform programmes and the implications for conditionality - Johnson, Omotunde E. G. (UN New YorkUS, 2005)
Argues that if the policies voluntarily adopted by a country were sound and if those policies are expected to be fully implemented and sustained - barring certain unforeseen exogenous developments - then traditional (policy-based) conditionality is not necessary for timely repayment of the money borrowed from the IMF, the World Bank, or any other creditor.